Aspectos socioambientais e legais da bananicultura na apa da na APA da Serra de Maranguape, estado do Ceará - Lima, Daniel Cassiano (2008)
This article addresses the problem of the irregular installation of banana plantations in Serra de Maranguape (CE), based on the Brazilian Environmental Legislation, and on the social and environmental conditions of banana growers. The research was developed based on the literature review and application of face-to-face and objective questionnaires. It was found that most of them had no schooling and were unaware of the seriousness of the consequences of banana cultivation in the mountains, as well as the authority of environmental agencies and law enforcement. Most of them have never worked in anything other than agriculture, although they carry out parallel activities, and most of them work in precarious conditions, without job guarantees. This is the first work that addresses the daily life and knowledge of banana growers about the Serra de Maranguape.